Peer-assisted motivation: a novel practical action research to combat absenteeism (Journal of Fatima Jinnah Medical University, 2019)
Background: Purpose of this study was to explore the causes of absenteeism in clinical lectures in 3rd year medical students and to find remedial measures for the same.Subjects and Method: Study was conducted in two research cycles from January 2016 to May 2017. First was multiphase mixed method inquiry for cause identification of absenteeism.  Second was practical action research (peer-assisted motivation), an intervention to combat absenteeism. Target population was 3rd year MBBS student of Quaid-e-Azam Medical College (QAMC), Bahawalpur, Pakistan. In first research cycle, two surveys for students, focus group discussions (FGDs) of fifteen students and five teachers, and interview of director Department of Medical Education (DME) were done. In next cycle, an intervention named peer assisted motivation (PAM) was employed to improve attendance.Results: In the first survey, 114 students participated. Analysis concluded that students don’t attend clinical lecture because they are busy in basic subjects and there is no examination for clinical subjects in 3rd year. The causes of truancy identified, in thematic analysis of FGDs and interview, were lack of motivation, administrative or technical issues, personal reasons and role of teachers. By triangulation and integration of data, a revise questionnaire was developed to be used in 2nd survey for 217 students, to retest old and quantify new themes. In PAM, thirty 4th year MBBS students motivated 3rd year students to attend clinical subject lectures. After intervention, attendance improved by 12.8%. The results were statistically significant (p ≤ 0.002).Conclusion: By using mixed method approach, absenteeism in clinical lectures in third year students is better understood. PAM was found to improve attendance and enhance interest in learning clinical subjects in third year students.
Keywords: Absenteeism; Causes; Peer-assisted motivation; Attendance; Undergraduate MBBS; Third year